UJI EFEKTIVITAS ANTIBAKTERI EKSTRAK DAUN RAMANIA (Bouea Macrophylla Griff) TERHADAP PERTUMBUHAN BAKTERI Streptococcus mitis - Lisa Shofa’ Nur Aini; Isyana Erlita; Didit Aspriyanto (Universitas Lambung Mangkurat, 2024)
Background: The presence of cavities causes bacterial invasion and spread of infection to the pulp tissue. If left untreated, infection will lead to pulpal necrosis. Root canal treatment can prevent caries from developing into necrosis. The success of treatment is influenced by the preparation and irrigation stages. One of the bacteria that survived after the treatment was Streptococcus mitis. The irrigation solution used in treatment is a 2% chlorhexidine gluconate. Ethanol extract from Ramania leaves is known to contain flavonoids, phenols, alkaloids, steroids and terpenoids which proven to have antibacterial activity. Objective: To analyze the antibacterial effectiveness of Ramania leaf extract concentrations of 10%, 15%, 20%, 25% and 30% against the growth of Streptococcus mitis . Methods: The research conducted was a true experimental study with 6 treatment groups and 4 repetitions. This study used broth and agar dilution methods to determine the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of ramania leaf extract against Streptococcus mitis. Results: The MIC was shown by 10% concentration with a decrease in absorbance value of 1.726. The MBC in this study were not found because there was still bacterial growth in the concentrations of 10%, 15%, 20%, 25% and 30%. Conclusion: Ramania leaf extract concentrations of 10%, 15%, 20%, 25% and 30% can inhibit the growth of Streptococcus mitis with MIC value at a concentration of 10%. The MBC value was not found because the extract had not been able to kill the growth of Streptococcus mitis. Keywords : MBC, MIC, Ramania Leaf Extract, Streptococcus mitis